Visual Signification in Thematic Concerns: A Semiotic Analysis - Malik Haqnawaz Danish; Abida Batool (Journal of Communication and Cultural Trends, 2019)
Visual narrative is a modern way of dispensing information or conveying a story to audience through elements with significations. Twenty first century is marked with the revolutionary trends of constructing narratives through images. Facebook and other social networking sites have made ‘image’ an easy way of communicating ideas, feelings and emotions. The researchers in the current study attempt to highlight the superiority of visual information using semiotic tools as the medium of decoding signs and their signification in elements appearing on a visual screen. Furthermore, the current research tries to elaborate the use of patterns, designs and concepts embedded in the video of the song by utilizing mise-en-scene, dexterously. The paper analyzes the visuals in the song by Sajjad Ali, ‘Tasveer Bana Kay’ semiotically, using Charles Peirce’ model and assigns signification to the elements of the visual text. The theme of the song is constructed through camera shot and angle, settings, colour and gestures and abstract ideas are metaphorically presented. Six images have been selected from the song video and analyzed semiotically. The current study establishes that a message can easily be conveyed with the help of images, amplifying the main theme of a narrative. The study gives an impetus to work on the genre of film studies and specially mise-en-scene as a supplementing device to communicate more than what is presented on the screen by decoding and constructing meaning which are implicitly explicit.